2012
DOI: 10.3389/fcimb.2012.00126
|View full text |Cite
|
Sign up to set email alerts
|

Growth conditions and environmental factors impact aerosolization but not virulence of Francisella tularensis infection in mice

Abstract: In refining methodology to develop a mouse model for inhalation of Francisella tularensis, it was noted that both relative humidity and growth media impacted the aerosol concentration of the live vaccine strain (LVS) of F. tularensis. A relative humidity of less than 55% had a negative impact on the spray factor, the ratio between the concentration of LVS in the aerosol and the nebulizer. The spray factor was significantly higher for LVS grown in brain heart infusion (BHI) broth than LVS grown in Mueller–Hinto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 19 publications
1
61
0
Order By: Relevance
“…For aerosol exposures, virulent F. tularensis strain SCHU S4 was grown as previously described using brain heart infusion (BHI) broth (28,29). After the exposures were completed, nebulizer and all-glass impinger (AGI) contents were quantified on cysteine heart agar (CHA).…”
Section: Methodsmentioning
confidence: 99%
“…For aerosol exposures, virulent F. tularensis strain SCHU S4 was grown as previously described using brain heart infusion (BHI) broth (28,29). After the exposures were completed, nebulizer and all-glass impinger (AGI) contents were quantified on cysteine heart agar (CHA).…”
Section: Methodsmentioning
confidence: 99%
“…, TNF, IL-1β, IL-6, IL-12, and IFN-γ) from a variety of cell-types within 24 h of in vitro infection, such T H 1-oriented molecules are absent during the first 72 h of in vivo infection [5], [14], [15]. Hazlett, et al [16] and others [17][20] have reported that in vitro growth conditions have a profound qualitative and quantitative effect on the in vitro as well as in vivo host response to Ft LVS and SchuS4. Ft cultivated under conditions that preclude host-adaptation ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The strains of B. pseudomallei and choice of culture medium were also different, which may contribute to the different results obtained in the two studies. It has been noted with F. tularensis and B. pseudomallei that culture conditions alter gene and protein expression, which can impact virulence and aerosolization (Chantratita et al, 2007;Hazlett et al, 2008;Faith et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria were grown first on solid media prior to an overnight culture in 25 ml liquid broth media using a baffled, vented 125 ml polycarbonate Erlenmeyer flask incubated in a bacterial shaker set at 200 r.p.m. Francisella tularensis SchuS4 strain was grown on cysteine heart agar (CHA Becton Dickinson, La Jolla, CA) for 2 days at 37 uC prior to culture in brain heart infusion broth (BHI; Becton Dickinson, La Jolla, CA) for 17-19 h at 37 uC (Faith et al, 2012). Burkholderia pseudomallei strain 1026b was grown on Luria-Bertani (LB; Becton Dickinson, La Jolla, CA) Agar for 1 day at 37 uC and then cultured overnight in BHI for 11 h at 37 uC.…”
Section: Methodsmentioning
confidence: 99%